Electricity and thermal physics - Ellse, Mark.; Honeywill, Chris (Cheltenham : Nelson Thornes, 2004)
This title includes examples from the prescribed specifications that are used to illustrate important principles. Information is presented in an accessible and concise user-friendly format for students of all abilities. Regular review questions stimulate thinking whilst topics are being studied. Appropriate practical investigation is provided with discussion questions to encourage analysis and evaluation. It includes typical exam questions, with mark schemes, to enable students to self-check for examinations.
Previous ed.: 2000.
Includes index.
Keywords: Heat; Heat -- Problems, exercises, etc; Electricity; Electricity -- Problems, exercises, etc